The role of bacteria in the pathogenesis and progression of idiopathic pulmonary fibrosis - Molyneaux,PL; Cox,MJ; Willis-Owen,SAG; Mallia,P; Russell,KE; Russel,A-M; Murphy,E; Johnston,SL; Schwarte,DA; Wells,AU; Cookson,WOC; Maher,TM; et al. (American Journal of Respiratory and Critical Care Medicine, 2014)
Rationale:Idiopathic pulmonaryfibrosis (IPF)isa progressivelung diseaseof unknown cause that leads to respiratory failure and death within 5 yearsof diagnosis. Overt respiratory infection and immunosuppression carrya high morbidity and mortality, and polymorphisms in genes related toepithelial integrity and host defense predispose to IPF.Objectives: To investigate the role of bacteria in the pathogenesisand progression of IPF.Methods: We prospectively enrolled patients diagnosed with IPFaccording to international criteria together with healthy smokers,nonsmokers, and subjectswithmoderate chronic obstructive pulmonarydisease as control subjects. Subjects underwent bronchoalveolarlavage (BAL), from which genomic DNA was isolated. The V3–V5region of the bacterial 16S rRNA gene was amplified, allowingquantification of bacterial load and identification of communities by 16SrRNA quantitative polymerase chain reaction and pyrosequencing. Measurements and Main Results: Sixty-five patients with IPFhad double the burden of bacteria in BAL fluid compared with 44 controlsubjects. Baseline bacterial burden predicted the rate of decline in lungvolume and risk of death and associated independently with thers35705950 polymorphism of the MUC5B mucin gene, a proven hostsusceptibilityfactorfor IPF. Sequencing yielded912,883 high-quality readsfrom all subjects.WeidentifiedHaemophilus, Streptococcus,Neisseria, andVeillonella spp. to be more abundant in cases than control subjects.Regression analyses indicated that these specific operational taxonomicunits as well as bacterial burden associated independently with IPF.Conclusions: IPF is characterized by an increased bacterial burdenin BAL that predicts decline in lung function and death. Trials ofantimicrobial therapy are needed to determine if microbial burdenis pathogenic in the disease.